An Investigation about the Natural Precursors of Disasters - SS, Praveen; KPK, Thulasi (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 8 No 3&4 (2021): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Natural disasters were a matter of things which were happening on the other side of the globe or planet especially for the people in Kerala. But disasters starting from 2004 Tsunami, 2017 Ockhi and 2018 floods exposed our vulnerabilities. Just before these disasters there were certain indications by the nature called as natural precursors. But the coastal community was not at all aware of such things and it contributed to the intensity of casualty. This paper is an attempt to identify and showcase those natural precursors during the event of above mentioned natural disasters which happened in Kerala and Tamilnadu. The investigation highlights the need for creating awareness about these kind of precursors especially among the coastal community. This investigation mentions several different, occurred precursors and briefly mentions about the science behind these precursors and urges the need for an in-depth scientific analysis incorporating large samples of heterogeneous nature, physical modelling and numerical modelling for unraveling the causative factors behind this. In-depth understanding about these kinds of precursors should be carried out and it should be backed with scientific evidence. The investigation recommends effective use of both official warnings and natural precursors for accelerating the mitigation activities prior to a disaster. How to cite this article: Praveen SS, Thulasi KPK. An Investigation about the Natural Precursors of Disasters. J Adv Res Alt Energ Env Eco 2021; 8(3&4): 1-5. DOI: https://doi.org/10.24321/2455.3093.202103